Синтез напівпровідникових тонких плівок цинк сульфіду і цинк селеніду. Огляд - Созанський, М. А.; Шаповал, П. Й.; Ятчишин, Й. Й.; Стаднік, В. Є.; Ларук, М. М.; Sozanskyi, M. A.; Shapoval, P. Yo.; Yatchyshyn, Yo. Yo.; Stadnik, V. E.; Laruk, M. M. (Lviv Politechnic Publishing House, 2018)
Проведено огляд основних фізичних і хімічних методів синтезу тонких плівок цинк сульфіду (ZnS) та цинк селеніду (ZnSe). Розглянуто кристалографічні характеристики цих сполук. Проаналізовано особливості виконання методів, їхні переваги та недоліки. Показано основні параметри отримання (температура, час осадження) плівок ZnS та ZnSe, їхні структурні, морфологічні властивості та товщину залежно від вибраного способу їхнього синтезу. Вивчено перспективи практичного використання хімічних методів. Аргументовано вибрано оптимальний метод хімічного осадження для одержання тонких плівок ZnS та ZnSe, які можна використати для заміни кадмійвмісних покриттів у буферних шарах фоточутливих елементів.

A review of the main physical and chemical methods of synthesis of zinc sulfide (ZnS) and zinc selenide (ZnSe) thin films was made. The crystallographic characteristics of these compounds are considered. The features of carrying out of methods, their advantages and disadvantages are analysed. The main parameters (temperature, deposition duration) of obtaining of ZnS and ZnSe thin films, their structural, morphological and thickness depending on the chosen method of their synthesis are shown. The possibilities of chemical methods practical use are studied. A well-reasoned choice of the optimal method of chemical deposition for obtaining of ZnS and ZnSe thin films, which can be used as a replacement of cadmiumcontaining in buffer layers of photosensitive elements, was made.
Synthesis of zinc sulfide and zinc selenide semiconductor thin films. Review
Keywords: цинк сульфід; цинк селенід; напівпровідникові плівки; хімічне осадження; морфологія поверхні; zinc sulfide; zinc selenide; semiconductor films; chemical deposition; surface morphology